Nutritional analysis of three balanced foods for puppies manufactured and marketed in Ecuador - Mena-Pérez, Renán (2021)
The aim of this study was to determine the nutritional quality of three “Premium” commercial foods for puppies manufactured and marketed in Ecuador, as well as to determine the sensitivity of the near infrared spectroscopy (NIRS) technique for the assessment of the macronutrients of these foods. The nutritional characteristics of three brands of food were analysed, taking samples from four batches per brand. The macronutrients (protein, fat, fibre, starch, ash and moisture) were determined using the NIRS technique, a test that was duplicated in two laboratories with different equipment. In addition, the amino acid profile was determined by liquid chromatography (HPLC). In the proximal analysis, the three foods meet the minimum macronutrient requirements to guarantee the development and health of the puppies, although one of them showed better nutritional composition. The NIRS technique as a rapid test is stable to analyse the components of dry pet food; however, it presented variability when measuring mainly the fat concentration (p=0.029) in the three foods, although it also occurred in one for fibre and ash contents. The concentration of non-essential and essential amino acids exceeded the minimum requirements established by international organizations in the three foods.